A study on determinants of the intention to use Islamic banking products in Johor Bahru / Norliyana Ahmad and Nur Atika Md Salleh - Ahmad, Norliyana; Md Salleh, Nur Atika (Faculty of Business and Management, 2014)
This study was conducted to investigate the determinants of the intention to use Islamic Banking products in Johor Bahru. Four independent variables had been identified which are religious beliefs, image and reputation, service quality and social influence. 282 respondents were involved in this research. The objectives of this study are to investigate the relationship between religious beliefs, image and reputation, service quality and social influence with the intention to use Islamic Banking products. Besides that, this study also determines the major factor that influences the intention to use Islamic Banking products. In order to ensure the objectives, researchers had use SPSS version 20. The result of this study shows that the significant variables that influence the intention to use Islamic Banking products. Besides that, social influence becomes the best predictor in the intention to use Islamic Banking products.